Problemy wyboru pomiędzy konkurującymi modelami wykładni prawa - Zirk-Sadowski, Marek (Wydawnictwo Uniwersytetu Wrocławskiego, 2016)
The plurality of theories of legal interpretation is well described in the legal literature. According to the author, the choice between the models of interpretation has to be based on the thesis that the full conception of the legal interpretation includes three levels of reflection: firstly, epistemology established for the theory of the interpretation, secondly, determining the relation between the theory of the interpretation and interpretative doctrine ius interpretandi and thirdly, structure of the theory of the interpretation which is a result of methodological solutions accepted by the type of jurisprudence. The paper has been devoted to discussing these three problems.
Keywords: teoria prawa; wykładnia prawa; interpretacja prawa